2014
DOI: 10.1088/0004-637x/783/2/125
|View full text |Cite
|
Sign up to set email alerts
|

TOWARD CONNECTING CORE-COLLAPSE SUPERNOVA THEORY WITH OBSERVATIONS. I. SHOCK REVIVAL IN A 15MBLUE SUPERGIANT PROGENITOR WITH SN 1987A ENERGETICS

Abstract: We study the evolution of the collapsing core of a 15 M blue supergiant supernova progenitor from the core bounce until 1.5 seconds later. We present a sample of hydrodynamic models parameterized to match the explosion energetics of SN 1987A.We find the spatial model dimensionality to be an important contributing factor in the explosion process. Compared to two-dimensional simulations, our three-dimensional models require lower neutrino luminosities to produce equally energetic explosions. We estimate that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 53 publications
7
82
0
Order By: Relevance
“…Lower (higher) energies produce lower (higher) iron velocities and lower (higher) X-ray fluxes at odds with the observations. We note that the explosion energies found are at the upper end of the range of values, E exp = 0.8 − 2.0 × 10 51 erg, proposed in the literature for SN 1987A (see Table 1 in Handy et al 2014). From bolometric lightcurve fitting what can be constrained is not the explosion energy itself but the ratio between the explosion energy, E exp , and the mass of hydrogen envelope, M env (e.g.…”
Section: Early Distribution and Mixing Of Ejecta In The Remnantmentioning
confidence: 72%
“…Lower (higher) energies produce lower (higher) iron velocities and lower (higher) X-ray fluxes at odds with the observations. We note that the explosion energies found are at the upper end of the range of values, E exp = 0.8 − 2.0 × 10 51 erg, proposed in the literature for SN 1987A (see Table 1 in Handy et al 2014). From bolometric lightcurve fitting what can be constrained is not the explosion energy itself but the ratio between the explosion energy, E exp , and the mass of hydrogen envelope, M env (e.g.…”
Section: Early Distribution and Mixing Of Ejecta In The Remnantmentioning
confidence: 72%
“…The calibration aims at producing the explosion energy and ejected 56 Ni mass of SN1987A compatible with observations, for which the best values are E exp =(1.50±0.12)×10 51 erg (Utrobin 2005), E exp ∼1.3×10 51 erg (Utrobin & Chugai 2011), and M Ni =0.0723-0.0772 M e (Utrobin et al 2014), but numbers reported by other authors cover a considerable range (see Handy et al 2014 for a compilation). The explosion energy that we accept for an SN1987A model in the calibration process is guided by the ejected 56 Ni mass (which fully accounts for short-time and long-time fallback) and a ratio of E exp to ejecta mass in the ballpark of estimates based on light-curve analyses (see Table 1 for our values).…”
Section: Progenitor Modelsmentioning
confidence: 99%
“…There is obviously justification for varying α turb within reasonable bounds on several grounds: While the underlying scaling law for the turbulent Mach number likely holds in 3D as well, the relevant dimensionless efficiency parameters (e.g. for turbulent dissipation) and hence α turb are bound to be slightly different, although the difference in α turb between 2D and 3D cannot be excessive given that the critical luminosity is very similar in both cases Dolence et al 2013;Couch 2013;Handy et al 2014). Moreover, since the record of 3D supernova simulations in obtaining explosions is mixed so far, and some crucial ingredients that boost the turbulent motions behind the shock may still be missing (such as strong seed perturbations from convective burning in the progenitor; Couch & Ott 2013;Couch et al 2015;, Finally, since our fits for the shock radius, and the advection and heating time-scales are already based on 2D and 3D simulations, and since the fits never perfectly reproduce the heating conditions in self-consistent models, α turb needs to be renormalised, and we will use values in the range α turb = 1.08 .…”
Section: Solution For the Shock Radiusmentioning
confidence: 99%